Penerapan Model Pembelajaran Problem Based Learning (PBl) untuk Meningkatkan Hasil Belajar Siswa Kelas 5 Sdn 060886 pada Materi Rantai Makanan - Ambarwati, Nova Florentina; Simanihuruk, Endang Ernawati; Daulay, Mita Suryani; Mahyuni, Mahyuni; Silalahi, Veni; Aisyah, Tuti; Aflah, Nurul (Indo-MathEdu Intellectuals Journal, 2025)
This classroom action research aims to improve the learning outcomes of fifth grade students of SDN 060886 on the food chain material through the application of the Problem Based Learning (PBL) learning model. The PBL model is applied to encourage students to be actively involved in the learning process by solving real problems relevant to the food chain topic. This research was conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of the research were fifth grade students of SDN 060886, with data collected through learning outcome tests, observation sheets, and interviews. Data analysis was carried out descriptively to see the increase in student learning outcomes from cycle to cycle. The results of the study showed that the application of the PBL model can significantly improve student learning outcomes. In cycle I, the average student score reached a fairly good category, while in cycle II, the average student score increased to a good category. In addition, student participation and motivation in learning also increased. Thus, the application of the Problem Based Learning learning model has proven effective in improving student learning outcomes on the food chain material. This study recommends the application of PBL as one of the learning strategies to improve the quality of the process and learning outcomes in elementary schools.